UJI SENSITIVITAS BEBERAPA ANTIBIOTIKA PADA JAMUR PENYEBAB KANDIDIASIS MULUT - Herman, Hendra (Jurnal Ilmiah As-Syifaa, 2011)
Has been done research Sensitivity Test of Several Antibiotic on  Candidiasis Mouth – Caused by mushroom. Kirby Bouer agar diffuse method used in this research, in which 15 specimen of acne were taken and performed three times replication to get a better result. Result of the research based on diameter of inhibitory zone showed that from three replication the antibiotic which sensitivity the most on   Candidiasis mouth – cause mushroom are Nystatin (60%), Griseofulvin (33,33%), Ketokenazol(26,67%), Flukonazol (26,67%) , Myconazol (6,67 %). The conclusion is antibiotic which sensitivity the most on Candidiasis mouth– caused by mushroom is Nystatin.   Key Words : Sensitivity Test, Antibiotic, Candidiasis Mouth.